The Impact of Financial Development on Economic Growth: A Case Study of Saudi Arabia - Saeed, Abdelrahman Mohamed (International Journal of Energy Economics and Policy, 2026)
The interrelation between economic growth and financial development has fuelled a debate in the area of economics. The financial development of countries is driven by the concert action of their governments regarding policy making, creating favourable financial infrastructure, and taking strategic initiatives for building a conducive financial sector. This study attempts to empirically assess the association between financial development and long-run growth in the context of Saudi Arabia. It uses select variables measured by the World Bank to predict economic growth and financial development. Furthermore, it analyses the link between financial development and economic growth in Saudi Arabia from 1980 to 2020, spanning a 40-year period. It uses a five-variable ARDL model using a supply-led approach. The Granger's test of causality and the VECM propose a unidirectional relationship flowing from the proxy of financial development to economic growth. This study's findings support the idea that financial development leads to economic growth in Saudi Arabia.